POSSIBLE WAYS OF DECREASE IN EMISSIONS OF CARBON DIOXIDE GAS - A. M. Gafurov; B. M. Osipov; R. Z. Gatina; N. M. Gafurov (Известия высших учебных заведений: Проблемы энергетики, 2018)
In article possible ways of decrease in emissions of carbon dioxide gas are considered. Features of technologies of extraction of CO2 from flue gases. Foreign experience of use of CO2 is analyzed. Possible ranges of application of CO2 as working medium for different heat engines and thermodynamic cycles are defined. Thermodynamic and heatphysical properties of carbon dioxide gas are investigated.